Color stability of visible light cured composite resin after soft drink immersion - Alizatul Khairani Hasan; Siti Sunarintyas; Dyah Irnawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2009)
Background: Composite resin is a tooth-colored filling material containing Bis-GMA which exhibits water sorption properties. People tend to consume soft drink with various colors. Water sorption properties can alter the color stability of composite resin purpose. Purpose: This study was to determine the influence of immersion durations of composite resin in soft drink on color stability. Methods: The visible-light cured hybrid composite resin and soft drink were used. Ten disk specimens (2.5 mm thickness and 15 mm diameter) of composite resin were prepared and light cured for 20 seconds, then stored in distilled water for 24 hours at 37° C. The initial color of specimens were measured by Chromameter. After that, each specimen was immersed in 30 ml of soft drink up to 48, 72, and 96 hours at 37° C. The specimens’ color were measured again after each immersion. The color changes were calculated by CIE L*a*b* system formula. The data was analyzed by One-Way ANOVA and LSD (α = 0.05). Result: The ANOVA showed that the immersion durations of composite resin in soft drinks had significant influence on the color stability (p < 0.05). The LSD0.05 tests showed significant differences among all groups. The least color change was detected from the group of 48 hours immersion, while the greatest color change was from the group of 96 hours immersion. Conclusions: The immersion of composite resin in soft drinks influenced the color stability (began after 48 hours immersion).